The Planning of Supply Requirments for Heavy Equipments and Costs Coal Mine to Reach The Production Target at Langkok Pit 1 Site PTBA UPO (Persero) Tbk, West Sumatra On 2017. - Nuzul Sandria Sasra; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT Bukit Asam (Persero) Tbk is a state-owned company engaged in the sector of a single market (captive market) which has 2 mining units, including the Ombilin Mining Unit (UPO) located in Ombilin, Sawahlunto, West Sumatra. Based on data from exploration of coal deposits carried out by PTBA UPO, one of the areas considered feasible to open is the Langkok Pit 1 UPO Site. Therefore, it is necessary to open a new mine so that the production target is reached. However, there is currently no planning for the needs of heavy equipment at the Langkok Pit 1 site. The purpose of this study is to determine the type and number of main tools and the costs needed. The research method used is the Applied Research method. In data analysis the calculation of the cycle time of mechanical devices is used to get the work productivity of the tool and the target of achieving hourly production of these mechanical devices and also as data in achieving the target mining plan per year. Mining activities used a combination of mining equipment, namely 1 Hitachi ZX330 excavator unit and 8 CWA 260MX UD dump truck units. The total rent that will be incurred per month in the needs of the equipment in August 2017 is Rp. 612.762.500,00 / month, in September is Rp. 637.273.000,00 / month, while in October it was Rp.588.252.000,00 / month, in November it was Rp. 637.273.000,00 / month, and December is Rp. 588.252.000,00 / month. So the total rental fee issued from August to December is Rp. 3.063.812.500,00. Keywords : Mining, Coal, Heavy Equipment, Costs, Production Targets